PERILAKU PELECEHAN SEKSUAL DAN PENCEGAHAN SECARA DINI TERHADAP ANAK - Sri Wahyuni (JURNAL RAUDHAH, 2016)
News of the behavior of sexual abuse increasing lately, then may need to provide information on how to actually such behavior to children early so that children understand the symptoms that can be seen children so that they can avoid its, while for parents can anticipate and prevent such behavior to the children and the possibility of higher number of sacrifice. To understand the symptoms that appear, then should also given the way or its prevention especially build communication so that the children are open in telling their activity day-to-day and confidence and courage when facing something actions that are perceived to be the son of uncomfortable.